2021
DOI: 10.3390/polym13142360
|View full text |Cite
|
Sign up to set email alerts
|

Extruded-Calendered Sheets of Fully Recycled PP/Opaque PET Blends: Mechanical and Fracture Behaviour

Abstract: This work presents the experimental results of the mechanical and fracture behaviour of three polymeric blends prepared from two recycled plastics, namely polypropylene and opaque poly (ethylene terephthalate), where the second one acted as a reinforcement phase. The raw materials were two commercial degrees of recycled post-consumer waste, i.e., rPP and rPET-O. Sheets were manufactured by a semi-industrial extrusion-calendering process. The mechanical and fracture behaviours of manufactured sheets were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Additionally, and considering the possibility of increasing this TiO 2 content, a mixture with a global content of 4% w / w of TiO 2 was evaluated to compare its performance. Details of this study could be found in [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, and considering the possibility of increasing this TiO 2 content, a mixture with a global content of 4% w / w of TiO 2 was evaluated to compare its performance. Details of this study could be found in [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…This effect is caused by the TiO 2 sub-micron particle cavitation, which allows a significant release of local triaxiality, promoting plastic the premature plastic tearing of the PET matrix [ 17 ]. Thus, one of the upgrading pathways proposed considered in this case study was to explore the use of r-O-PET as a reinforcement for recycled polypropylene (r-PP) matrix, inducing a microfibrillation of the PET phase during processing that acts as reinforcing fibres, under the manufacturing philosophy of in situ microfibrilated composites (MFC) [ 18 ]. According to his study, the blend composition that offers the best balance of mechanical properties and fracture behaviour of the MCM produced is the one with 20% w / w of r-O-PET.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide powders functionalized with nanosilica for wear resistence applications [30] Ángel Alvaredo-Atienza Juan P. Fernández-Blázquez Fabrication and characterization of PEEK/PEI multilayer composites by alternate layer stacking [31] David Loaeza Orlando Santana Pérez, Maria Lluïsa Maspoch Polymeric blends prepared from two recycled plastics, polypropylene and opaque poly(ethylene terephthalate), acting as reinforcement [32] Vanessa García Vanessa García-Martínez, Alejandro Ureña…”
Section: Synthesis Of New Monomers Polymers and Compositesmentioning
confidence: 99%
“…Such reinforcement increases the fatigue life of this blend eightfold. 10 Waste PET fabric acts as a reinforcement in the adhesive layer for improving the flexural properties of a bi-layer laminate bonded with rPP based adhesive. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Such reinforcement increases the fatigue life of this blend eightfold. 10 Waste PET fabric acts as a reinforcement in the adhesive layer for improving the flexural properties of a bi-layer laminate bonded with rPP based adhesive. 11,12 Moisture absorption capacity of rPP/rPET blend is lesser than the rPet alone and the compatibilized rPP/rPET blend.…”
Section: Introductionmentioning
confidence: 99%